Describing Ion Exchange at Membrane Electrodes for Ions of Different Charge. Issue 4 (4th December 2017) - Zdrachek, Elena; Bakker, Eric
Abstract: It is well‐documented in the literature that the Nikolsky‐Eisenman equation cannot accurately describe the equilibrium of ion exchange at membrane electrodes for ions of different charge. Despite this, unfortunately, it is still widely used owing to the complexity of the more rigorous formalism developed by Bakker et al. in 1994. Here, different available approaches are presented in a unified manner and compared. This includes two different approximations that are equally appropriate for cases of low level of interference where the extent of ion‐exchange is comparatively small, one of which is introduced here for the first time. The comparison also considers the permutated form of the Nikolsky‐Eisenman equation, where the primary ion is treated as the interfering ion and vice versa. As the permutated form gives a deviation from the thermodynamic model that is opposite that of the regular Nikolsky‐Eisenman equation, the two can be combined to give a semi‐empirical equation that is surprisingly close to the thermodynamic model and that comprises a single equation for any charge combination. The different choices presented here may be helpful to solve more complex theoretical problems, as for example in the modeling of the time dependence of the electrode response by numerical simulation where the interfacial step condition is a unique and difficult feature of the calculation. Abstract :